2017
DOI: 10.1523/eneuro.0388-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Neurodevelopmental and Neurodegenerative Pathology inNhe6-Null Mouse Model of Christianson Syndrome

Abstract: Christianson syndrome (CS) is an X-linked disorder resulting from loss-of-function mutations in SLC9A6, which encodes the endosomal Na+/H+ exchanger 6 (NHE6). Symptoms include early developmental delay, seizures, intellectual disability, nonverbal status, autistic features, postnatal microcephaly, and progressive ataxia. Neuronal development is impaired in CS, involving defects in neuronal arborization and synaptogenesis, likely underlying diminished brain growth postnatally. In addition to neurodevelopmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 34 publications
8
29
0
Order By: Relevance
“…Postmortem examination of 2 CS males in their 40s and 50s found widespread neuronal and glial loss, as well as accumulation of tau-positive tangle-like inclusions [9]. Furthermore, neurodegenerative features have been reported in an Nhe6 -null mouse model such as loss of Purkinje cells in the cerebellum, loss of tissues and synapses, and a strong microglial response [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Postmortem examination of 2 CS males in their 40s and 50s found widespread neuronal and glial loss, as well as accumulation of tau-positive tangle-like inclusions [9]. Furthermore, neurodegenerative features have been reported in an Nhe6 -null mouse model such as loss of Purkinje cells in the cerebellum, loss of tissues and synapses, and a strong microglial response [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Less severe neuronal loss and gliosis have been documented in other brain regions, such as the cerebral cortex and hippocampus (6). Similar degeneration of the cerebellum and mild undergrowth and atrophy of the hippocampus, striatum, and cortex were also observed in Slc9a6 knockout mice (32,34,35). The variable penetrance and seemingly selective deterioration of certain neuronal populations upon loss of NHE6 function, despite its broad expression throughout the CNS, is not well understood but may reflect the nature of the mutation as well as other ill-defined genetic-modifier effects or compensatory mechanisms.…”
Section: Expression Of Defective Nhe6 Variants Reduces Cell Viabilitymentioning
confidence: 66%
“…Previous studies have revealed that genetic disruption of NHE6 expression causes degeneration of a subset of neurons within the cortex, hippocampus and especially the cerebellum which exhibits extensive Purkinje cell loss with age (32,34,35). Neurons in other brain regions, despite the loss of NHE6 expression, do not appear as severely affected.…”
Section: Effect Of Nhe6 Variants On Cell Viabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with a role in amyloid pathology, in vivo Aβ levels were found to be significantly higher in the brains of NHE6 KO mice. These findings could have implications for Christianson 5 syndrome patients who have loss of function mutations in NHE6 and exhibit agedependent hallmarks of neurodegeneration 17, 18 . In summary, we identify NHE6 as a novel ApoE effector and suggest potential therapeutic options in the treatment of amyloid disorders.…”
Section: Introductionmentioning
confidence: 94%